Utilisation of the Australian government initiative MyHealth Record to support the clinical approach to factitious disorder. Issue 8 (6th August 2020) - Alchin, David R.; Overton, Kristen; George, Duncan; Murphy, Michael; Wand, Anne P. F.
Abstract: Recently, the Australian Digital Health Agency launched MyHealth Record to the public. As of July 2019, 90.1% of Australians hold records with this service, allowing 16 400 health organisations access to >28 million clinical documents. The streamlining of patient data was intended to facilitate sharing of information and improve communication between medical providers, while promoting efficiency in clinical practice. We have identified a hitherto unrecognised application of this infrastructure in the identification and management of factitious disorder, a rare yet highly diagnostically challenging condition involving intentional feigning of illness, which presents a significant resource burden to the Australian health system.